Vergesellschaftung unter Ansteckenden – für eine Körpergeschichte der Seuche - Dross, Fritz (NTM Zeitschrift für Geschichte der Wissenschaften, Technik und Medizin, 2020)
This paper is part of Forum COVID-19: Perspectives in the Humanities and Social Sciences. Being a “trauma of mankind” epidemics have been a major subject of historical research for a long time and regarding every historical period. Recurring to the concept of Rudolf Schlögl (“Vergesellschaftung unter Anwesenden”) my proposal is to research epidemics as a history of the communicating body and thus including the contagium as part of this communication.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Communication; Disease; Epidemic; Infection